P437 Diagnostic utility of serum beta D glucan test to prescribe antifungal treatment and its effect on patient's outcome: a study from a tertiary care center in Western India. (20th September 2022) - Patel, Kamlesh; Barot, Nidhi; Patel, Ketan; Kumar, Ambuj; Patel, Atul
Abstract: Poster session 3, September 23, 2022, 12:30 PM - 1:30 PM: Serum Beta D glucan has 75%-80% sensitivity and 80% specificity to make a diagnosis of invasive candidiasis. Objectives: This study was designed to understand real-world diagnostic utility of S. Beta D Glucan (BDG) on antifungal prescription patterns associated patient outcomes. Methods: Study design: Retrospective cohort study Study Population: All consecutive patients who underwent BDG (fungitell assay) testing with conclusive (positive or negative) results in the intensive care unit (ICU) setting between January 1, 2021 to December 31, 2021 at a tertiary care center in western India. Statistical Methods: We assessed the difference in continuous variables across compared groups using the independent samples t -test and binary logistic regression for categorical variables. We summarize the summary results as odds ratio and 95% confidence intervals. All P -values are 2-sided and set at 5% for all comparisons. All data analyses were performed using IBM SPSS ver 28. Results: A total of 4481 patients were admitted in the ICU, of which 198 patients underwent BDG testing. Of the 198, 113 tested positive and 61 negative and formed the denominator for the study. Patients with intermediate BDG [24 (12.1%)] were excluded from the analysis. The mean (SD) age for the study cohort was 57.5 (14.7) years with 30.8% female. All the patients were receiving broad-spectrum antibiotics at the time of BDG collection. A total of 24 study patients had a positive blood culture (23 bacterial isolates and 1 Candida parapsilosis ). The groups, positive and negative test results for BDG, were comparable for ventilator usage ( P  = .737), vasopressor prescription ( P  = .270), history of surgery ( P  = .791) central line placement ( P  = .403), liver disease ( P  = .144), CKD ( P  = .424), COVID-19 positivity ( P  = .238), WBC count ( P  = .137), CRP ( P  = .769), and serum procalcitonin ( P  = .784). Patients with ischemic heart diseases (IHD) ( P  = .013) and acute kidney injury requiring hemodialysis (AKI/HD) ( P  = .017) were significantly higher in the test positive group. Test negative group patients received early BDG testing, mean (SD) stay of 3.33 (3.77) days as compared to 5.61 for test positive (6.59) days P  = .004). More test-positive patients received antifungal therapy ( P  <.0001), while 20.4% didn't receive antifungals. Caspofungin (25.9%), fluconazole (18.4%), anidulafungin (7.5%), voriconazole (6.9%), and combination antifungal were used in 10.9% of study patients. Logistic regression model showed no difference in mortality between the two groups ( P  = .413) with higher Odds of mortality in test-positive patients (1.357, 95% CI 0.705- 2.609). Treatment with caspofungin was associated with higher Odds of mortality (3.497; 95% CI 1.324–9.239, P  = .012) as compared with fluconazole. Similar trend was observed with anidulafungin (OR: 4.089 95% CI 1.052-15.888, P  = .042) as compared to fluconazole. This significance remained for caspofungin [OR 3.607 (1.262 -10.311) P  = .017] while anidulafungin [OR: 3.934 (0.965-16.032) P  = .56] didn't show significance with the multivariate model. Conclusion: Probable invasive candidiasis as diagnosed with positive BDG test doesn't increase the risk of mortality. Patients treated with fluconazole were associated with better survival as compared with caspofungin.